Asynchronous programming in JavaScript : complete course. (Packt Publishing, 2022)
Delve deep into the exciting world of asynchronous programming, especially with JavaScript as your language of choice. About This Video Learn one of the most complex topics of programming with easy-to-understand examples and hands-on explanations Learn about callbacks and how you have been using them in your daily programming already Learn all about event loops and how JavaScript works behind the screen and how it executes asynchronous code In Detail JavaScript was not designed to be an asynchronous language, but with just the right tweaks, you can make it asynchronous. Asynchronous code helps you manage everything seamlessly while making sure that the data you are waiting for is used in your code ONLY after it has been completely fetched. In this course, you will learn every single concept of asynchronous JavaScript with easy-to-understand, over-the-shoulder examples and detailed, interesting explanations. You will learn all about event loops and how JavaScript works behind the screen and how it executes asynchronous code, about callbacks and their drawbacks, how promises replaced them and how Async Await made promises prettier. You will apply all of these in three real-world mini-projects as well. We will look at Async Await, an ES7 update, and how they have made promises look pretty. We will also look at resolving multiple promises at the same time using Async Await and error handling. By the end of this course, you will have a thorough understanding of how asynchronous programming works in JavaScript. Audience This course has been designed for JavaScript developers who want to take their knowledge to the next level; web developers who would like to add "asynchronous programming" to their resume and stand out in their job interviews; programmers and fledgling developers who would like to learn how real-world programming works; and front-end developers who are working with frameworks such as Angular, React, Vue, or Svelte and would like to apply asynchronous programming concepts in their projects. Some knowledge of JavaScript will be an added advantage to get through the course.